Role of electrostatic interactions in the toxicity of titanium dioxide nanoparticles toward Escherichia coli - Pagnout, Christophe; Jomini, Stéphane; Dadhwal, Mandeep; Caillet, Céline; Thomas, Fabien; Bauda, Pascale (Colloids and surfaces, B, Biointerfaces, 2012)
[Display omitted] ► NP-TiO2 may affect the viability of Escherichia coli in the absence of light. ► Interfacial electrostatic interactions play a paramount role in the toxicity. ► Physico-chemical parameters are fundamental in controlling the interactions. ► This study provides knowledge essential to a better assessment of NP toxicity. The increasing production and use of titanium dioxide nanoparticles (NP-TiO2) has led to concerns about their possible impact on the environment. Bacteria play crucial roles in ecosystem processes and may be subject to the toxicity of these nanoparticles. In this study, we showed that at low ionic strength, the cell viability of Escherichia coli was more severely affected at pH 5.5 than at pH 7.0 and pH 9.5. At pH 5.5, nanoparticles (positively charged) strongly interacted with the bacterial cells (negatively charged) and accumulated on their surfaces. This phenomenon was observed in a much lower degree at pH 7.0 (NP-TiO2 neutrally charged and cells negatively charged) and pH 9.5 (both NP-TiO2 and cells negatively charged). It was also shown that the addition of electrolytes (NaCl, CaCl2, Na2SO4) resulted in a gradual reduction of the NP-TiO2 toxicity at pH 5.5 and an increase in this toxicity at pH 9.5, which was closely related to the reduction of the NP-TiO2 and bacterial cell electrostatic charges.